EKSPOSISI EFESUS 5:22—6:4 TENTANG NILAI-NILAI KEHIDUPAN DALAM KELUARGA KRISTEN - Yohanna Cristiani Oktavia Malau (JURNAL PENABIBLOS, 2019)
Family conflicts are normal and can be a creative power in marriage. Conflict will arise due to family member interaction. Interpersonal conflict in the family is a conflict of problems that occur between members in one family because of the difference in intent or purpose shown in different ways as well. Conflict that happened to husband and wife, parents-children, children and other family members that exist in one household. But the end result of a conflict, whether it will be destructive or constructive? This will largely depend on what strategy will be used to handle or manage the conflict itself. In this article, the author will investigate and explain Ephesians 5:22—6:4 to find the values of life in a Christian family that can be used as a standard in building relationships and responsibilities in a Christian family. Through this explanation it is hoped that each reader can understand their respective roles and responsibilities in a family. A correct understanding of these truths can minimize the possibility of conflict in the family. The method used in writing this article is the explanation of the text by using the principles of hermeneutics that apply, then the writer makes the principles that can be compiled into the application of each individual.